Pharmacokinetics of novel Fc-engineered monoclonal and multispecific antibodies in cynomolgus monkeys and humanized FcRn transgenic mouse models - Delphine Valente; Christine Mauriac; Thorsten Schmidt; Ingo Focken; Jochen Beninga; Brian Mackness; Huawei Qiu; Pascale Vicat; Abdullah Kandira; Katarina Radošević; Srini Rao; John Darbyshire; et al. (Taylor & Francis Group, 2020)
Monoclonal antibodies (mAbs) are among the fastest growing and most effective therapies for myriad diseases. Multispecific antibodies are an emerging class of novel therapeutics that can target more than one tumor- or immune-associated modulators per molecule. The combination of different binding affinities and target classes, such as soluble or membrane-bound antigens, within multispecific antibodies confers unique pharmacokinetic (PK) properties. Numerous factors affect an antibody's PK, with affinity to the neonatal Fc receptor (FcRn) a key determinant of half-life. Recent work has demonstrated the potential for humanized FcRn transgenic mice to predict the PK of mAbs in humans. However, such work has not been extended to multispecific antibodies. We engineered mAbs and multispecific antibodies with various Fc modifications to enhance antibody performance. PK analyses in humanized FcRn transgenic mouse (homozygous Tg32 and Tg276) and non-human primate (NHP) models showed that FcRn-binding mutations improved the plasma half-lives of the engineered mAbs and multispecific antibodies, while glycan engineering to eliminate effector function did not affect the PK compared with wild-type controls. Furthermore, results suggest that the homozygous Tg32 mouse model can replace NHP models to differentiate PK of variants during lead optimization, not only for wild-type mAbs but also for Fc-engineered mAbs and multispecific antibodies. This Tg32-mouse model would enable prediction of half-life and linear clearance of mAbs and multispecific antibodies in NHPs to guide the design of further pharmacology/safety studies in this species. The allometric exponent for clearance scaling from Tg32 mice to NHPs was estimated to be 0.91 for all antibodies.